The Relationship Between Gender Schema and Dysfunctional Sexual Beliefs with the Mediating Role of Psychological Hardiness in Women - Sarkhosh, Soodabeh; Amini, Naser; Keykhosrovani, Moloud (KMAN Counseling & Psychology Nexus, 2026)
The present study aimed to examine the relationship between gender schema and dysfunctional sexual beliefs with the mediating role of psychological hardiness in married women. This study employed a descriptive-correlational design using structural equation modeling (SEM). The statistical population consisted of all married women aged 30 to 40 years working in official and governmental bank branches in Bushehr in 2025. A sample of 266 participants was selected through convenience sampling based on Cochran’s formula. Data were collected using the Dysfunctional Sexual Beliefs Questionnaire (SDBQ), the Bem Sex Role Inventory (BSRI), and the Ahvaz Psychological Hardiness Inventory (APHI). Data analysis was conducted using SPSS version 28 for descriptive statistics and correlation and regression analyses, and AMOS software for testing the structural model and mediating effects. The results indicated that masculinity (β = 0.22, p = 0.017) and femininity (β = 0.26, p = 0.010) had positive and significant effects on dysfunctional sexual beliefs, while the effect of neutral gender schema was not significant (β = -0.09, p = 0.212). Masculinity (β = -0.34, p = 0.010) and femininity (β = -0.28, p = 0.010) had significant negative effects on psychological hardiness, whereas neutral traits showed no significant effect (β = 0.08, p = 0.432). Psychological hardiness had a significant negative effect on dysfunctional sexual beliefs (β = -0.39, p = 0.010). Additionally, the indirect effects of masculinity (β = 0.13, p = 0.050) and femininity (β = 0.11, p = 0.050) on dysfunctional sexual beliefs through psychological hardiness were significant, while the indirect effect of neutral traits was not significant (β = -0.03, p = 0.268). The findings highlight the significant role of gender schema dimensions and psychological hardiness in shaping dysfunctional sexual beliefs, emphasizing that psychological hardiness partially mediates the relationships between masculinity and femininity with dysfunctional sexual beliefs, and suggesting that enhancing resilience and promoting flexible gender schemas may reduce maladaptive sexual beliefs in women.